EFEKTIVITAS KEBIJAKAN SISTEM PENGGAJIAN PERANGKAT DESA DALAM MENINGKATKAN PRODUKTIVITAS DAN DISIPLIN KERJA (STUDI KASUS PEMDES KEBUNDADAP BARAT) - Prasetiyo, M. Ferdiyansah; Abrar, Unsul (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2022)
Salary is a component of compensation that should be given to an employee or staff by a company as a form of remuneration for what the employee gives to the company as an attempt to increase productivity in working as well as work discipline. This study was conducted towards a village government of West Kebundadap which is a community service place by using purposive sampling technique encompassing 11 informants as information sources. The data analysis technique of Miles and Huberman model consists of Data Reduction, Data Presentation, and Conclusion. The researcher found a problem of incongruity of set salary payment time. The finding shows that salary does not always play a role to increase productivity and work discipline, because different workplaces generate different work purposes. Although the salary payment for village government staffs of West Kebundadap is often not on time, they still can manage to be productive and discipline in working due to the reason of community trust but most of them do not prioritize their profession as village apparatus in order to make ends meet when the salary is not paid yet.